2008
DOI: 10.1063/1.2990055
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction of cholesteric liquid crystal gratings probed by monochromatic light from 450 to 750 nm

Abstract: We investigated both theoretically and experimentally the diffraction property of cholesteric liquid crystals (CLCs) in the configuration of transmission grating. The CLCs are treated as birefringent index gratings whose diffraction property is strongly dependent on the polarization state of the incident beam. In our experimental studies, the CLC index gratings are constructed by applying an electric voltage to liquid crystal cell. The grating is probed by a monochromatic light in spectral range from 450 to 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…There are three different modes. In the homogeneous cell [ 1 , 2 , 3 , 4 , 5 , 6 ], which is composed of two substrates with parallel alignment, the LC molecules spontaneously organize into planar helical layers with the helical axis perpendicular to the substrates. As illustrated in Figure 1 a, the helical pitch P is defined as the length of one turn of the helical structure.…”
Section: Introductionmentioning
confidence: 99%
“…There are three different modes. In the homogeneous cell [ 1 , 2 , 3 , 4 , 5 , 6 ], which is composed of two substrates with parallel alignment, the LC molecules spontaneously organize into planar helical layers with the helical axis perpendicular to the substrates. As illustrated in Figure 1 a, the helical pitch P is defined as the length of one turn of the helical structure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the polarization sensitivity of the CLC grating is also investigated. As shown in Figure 3d, it is obvious that the spots diffracted from stripes parallel to the incident polarization possess higher intensity than those diffracted from orthogonal stripes, stemming from the optical anisotropy of the LCs and the periodic lying-helix structure inside the CLC grating [16,36,37]. Besides checkerboard hierarchical gratings, more complex and photo-responsive CLC hierarchical gratings are fabricated by rationally designing the alignments.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that not only electric field but also light is capable of generating periodic patterns in CLCs doped with photoresponsive dyes . Hung et al prepared transmission gratings by applying electric field to a planar aligned CLC and probed their characteristics by monochromatic radiation with wavelengths spanning across the visible spectrum …”
Section: Control Of the Helical Axis Of Clcs By Different Stimulimentioning
confidence: 99%